Efficient Piezoelectric Energy Harvesters Utilizing (001) Textured Bimorph PZT Films on Flexible Metal Foils. (7th June 2016) - Yeo, Hong Goo; Ma, Xiaokun; Rahn, Christopher; Trolier‐McKinstry, Susan
Abstract : Extracting energy from low vibration frequencies (<10 Hz) using piezoelectric energy harvester promises continuous self‐powering for sensors and wearables. The piezoelectric compliant mechanism (PCM) design provides a significantly higher efficiency by fostering a uniform strain for its 1st mode shape, and so is interesting for this application. In this paper, a PCM energy harvester with bimorph Pb(Zr, Ti)O3 (PZT) films on Ni foil deposited by rf magnetron sputtering is shown to have high efficiency and large power for low frequency mechanical vibration. In particular, 001 textured PZT films are deposited on both sides of polished Ni foils with (100) oriented LaNiO3 seed layers on HfO2 buffer layers. The performance of PCM with an active area of 5.2 cm 2 is explored for various excitation accelerations (0.02–0.16 g [g = 9.8 m s −2 ]) around 6 Hz. The PCM device provides a power level of 3.9 mW cm −2 g 2 and 65% mode shape efficiencies. Abstract : (001) textured PZT films are deposited on both sides of a Ni foil to produce a high energy harvesting figure of merit. This is coupled with a novel mechanical design that more efficiently strains the piezoelectric material in response to mechanical excitation. The resulting energy harvester has a low resonant frequency ≈6 Hz, that matches the ambient mechanical energy spectrum well, and a very high energy density.